1993
DOI: 10.1111/j.1365-2052.1993.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of susceptibility to Marek's disease within the major histocompatibility (B) complex by refined typing of White Leghorn chickens

Abstract: The major histocompatibility ( B ) complex of a distinct commercial pure White Leghorn chicken line was characterized using serological, biochemical and restriction fragment length polymorphism (RFLP) typing. Line B chickens displayed a high recombination frequency within the B complex. Three recombinant haplotypes were identified. The influence of these haplotypes was determined in relation to the haplotypes B" and BZ1 on their resistance to Marek's disease (MD) in an experimental infection with the virus. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In the chicken, the MHC-B region has an exceptionally strong role in genetic resistance to Marek's disease (MD) caused by gallid herpesvirus-2 (GaHV-2) and to Rous sarcoma virus (RSV)-induced tumors (1,2). Resistance to these diseases maps to the MHC-B subregion marked by a highly expressed classical MHC class I gene (3)(4)(5)(6). It has been suggested that strong MHC-B disease associations are apparent as the result of alleles at this single locus for classical class I antigen presentation, BF2, contributing to immune responses either independently or in concert with closely-linked transporter associated with antigenprocessing (TAP) genes (6,7).…”
mentioning
confidence: 99%
“…In the chicken, the MHC-B region has an exceptionally strong role in genetic resistance to Marek's disease (MD) caused by gallid herpesvirus-2 (GaHV-2) and to Rous sarcoma virus (RSV)-induced tumors (1,2). Resistance to these diseases maps to the MHC-B subregion marked by a highly expressed classical MHC class I gene (3)(4)(5)(6). It has been suggested that strong MHC-B disease associations are apparent as the result of alleles at this single locus for classical class I antigen presentation, BF2, contributing to immune responses either independently or in concert with closely-linked transporter associated with antigenprocessing (TAP) genes (6,7).…”
mentioning
confidence: 99%
“…Disease resistance of poultry to a number of avian viruses, such as Marek's disease virus (Bacon et al, 2001;Hepkema et al, 1993), Rous sarcoma virus (Aeed et al, 1993;Collins et al, 1977;Taylor, 2004), avian leukosis virus (Yoo and Sheldon, 1992), infectious bursal disease virus (Fadly and Bacon, 1992), AIV (Hunt et al, 2010) and Newcastle disease virus (Dunnington et al, 1992), has been associated with the MHC B region. The DNA sequencing of the MHC I (B-F) and MHC II (B-L) genes indicated that, although promoters of the avian are very similar, enhancer A sequences vary for the B2, B4, B8 and B21 haplotypes and are missing entirely in the B12 and B19 haplotypes (Kaufman et al, 1999;Miller et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the expression of a single gene could result in differences in resistance and susceptibility to infectious pathogens in individuals with different MHC haplotypes (Hepkema et al. ; Kaufman ).…”
Section: Discussionmentioning
confidence: 99%
“…Also variations in the level of polymorphism have been found to differ among bird species, thus some species with a unique class II B loci had more alleles than a species with more loci (Hughes et al 2008). Thus, the expression of a single gene could result in differences in resistance and susceptibility to infectious pathogens in individuals with different MHC haplotypes (Hepkema et al 1993;Kaufman 2000).…”
Section: Mhc Diversitymentioning
confidence: 99%